Androgenic effects of alcoholic extract from Cnidium monnieri (L.) Cuss fruits in experimental animals - Duong, Dau Thuy; Huong, Nguyen Tran Thi Giang; Ha, Le Minh; Van Anh, Pham Thi; Trang, Tran Quynh (Tạp chí Nghiên cứu Y học, 2024)
Traditional medicine used the fruits of Cnidium monnieri (L.) Cuss to treat male hypogonadism and male infertility. This study was carried out to investigate the potential androgenic properties of the alcoholic extract of Cnidium monnieri (L.) Cuss fruits (CFE) in peripubertal castrated male rats. Rats were randomly divided into 5 groups and castrated 7 days before being administered 0.5% CMC, testosterone and CFE at 50 mg/kg/day, 150 mg/kg/day and 250 mg/kg/day, respectively, for 10 days. The relative weight of five target androgen-dependent organs (including seminal vesicles (SV), ventral prostate (VP), paired Cowper’s glands (COW), glans penis (GP) and levator ani-bulbocavernosus (LABC) muscle and blood testosterone level were evaluated. Our results showed that CFE at 150 mg/kg/day and 250 mg/kg/day increased the weights of two or more target organs and blood testosterone level. In conclusion, CFE at both doses of 150 mg/kg/day and 250 mg/kg/day has the androgenic activity in male rats.